2017
DOI: 10.1002/eco.1800
|View full text |Cite
|
Sign up to set email alerts
|

Spatial clusters and temporal trends of seasonal surface soil moisture across China in responses to regional climate and land cover changes

Abstract: Investigating the spatiotemporal changes of regional surface soil moisture in responses to climate and land cover changes is vital for understanding the underlying mechanisms of hydrological processes. While previous studies mainly attributed the causes of soil moisture changes to climatic factors, few took land cover into consideration. We analyzed the seasonal-differentiated effects of climate and land cover changes on surface soil moisture of China's 80 drainage basins using the Essential Climate Variable S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…Feng (2016) assessed the drivers of trends in ESA CCI SM COMBINED v02.2 and concluded that at the global scale climate change is by far the most important driver of long-term changes in soil moisture, although at the regional level land cover and land use change may play a significant role. Similar conclusions were drawn by regional studies over China (Chen et al, 2017;Liu et al, 2015;Meng et al, 2017). Other studies analysed the variability and trends in ESA CCI SM in relation to other atmospheric variables and circulation patterns over Asia (Shrivastava et al, 2016(Shrivastava et al, , 2017Zhan et al 2017).…”
Section: Climate Variability and Changesupporting
confidence: 76%
“…Feng (2016) assessed the drivers of trends in ESA CCI SM COMBINED v02.2 and concluded that at the global scale climate change is by far the most important driver of long-term changes in soil moisture, although at the regional level land cover and land use change may play a significant role. Similar conclusions were drawn by regional studies over China (Chen et al, 2017;Liu et al, 2015;Meng et al, 2017). Other studies analysed the variability and trends in ESA CCI SM in relation to other atmospheric variables and circulation patterns over Asia (Shrivastava et al, 2016(Shrivastava et al, , 2017Zhan et al 2017).…”
Section: Climate Variability and Changesupporting
confidence: 76%
“…Soil moisture dynamics are closely related to changes of precipitation [15,[39][40][41] which is the main source of SM. During the 1979-2016 period, annual precipitations have significantly changed in 15% of the valid global lands except in the Amazon and Congo River basins.…”
Section: Influence Of Precipitationmentioning
confidence: 99%
“…The surface temperature of the sea https://www.esrl.noaa.gov/psd/data/gridded [28][29][30][31] Ice coating https://www.ecmwf.int/en/research/modellingand-prediction/marine [32][33][34] Monthly average long-wave radiation https://climatedataguide.ucar.edu/climatedata/outgoing-longwave-radiation-olr-hirs [14,35,36] Monthly average near-infrared beam downward sun flux https://climatedataguide.ucar.edu/climatedata/outgoing-longwave-radiation-olr-hirs [37,38] Average monthly precipitation https://www.esrl.noaa.gov/psd/cgi-bin/data/ getpage.pl [32,39] Monthly average evaporation rate https://www.esrl.noaa.gov/psd/data/gridded [27,[39][40][41][42][43] Earth surface wind speed https://www.esrl.noaa.gov/psd/data/gridded [6,43] Earth surface cloud amount https: //www.ecmwf.int/en/forecasts/datasets/set-i [44] Average temperature https://climate.weather.gc.ca [5,45,46] Relative humidity https: //www.ecmwf.int/en/forecasts/datasets/set-i [7,45] Total carbon dioxide emissions https://www.ecmwf.int/en/annual-report-2014/ developing-european-infrastructure [47] Soil moisture https://www.esrl.noaa.gov/psd/data/gridded [48,49] Land-sea mask https://www.esrl.noaa.gov/psd/data/gridded [38] Mean sea level pressure https://www.esrl.noaa.gov/psd/data/gridded [50] Snow density https: //www.ecmwf.int/en/forecasts/datasets/set-i [38] Total column ozone https: //www.ecmwf.int/en/forecasts/datasets/set-i [51] Cooling degree-days https://climatedataguide.ucar.edu/climatedata/outgoing-longwave-radiation-olr-hirs …”
Section: Indicators Official Source Literature Sourcementioning
confidence: 99%